The Impact of Implementing a Zonasi System on the Acceptance of New Students in Junior High School in Yogyakarta - Riswan, Riswan; Wibowo, Udik Budi (Asia Pacific Journal of Management and Education (APJME), 2020)
The purpose of this study is to explore the impact of applying the zonasi system policy on New Student Admissions (PPDB) in Junior High Schools (SMP). This study uses a qualitative approach with field observation techniques, documentation, and interviews. The results showed that the implementation of the zonasi system in PPDB in junior high schools had positive and negative impacts are: 1) the positive impact of the zoning system policy is to make schools more sensitive to the diverse needs of students. In addition, every teacher must be able to improve his quality at the time of learning related to the varied abilities of students, and 2) helped students with low minimum test score obtain an education. The negative impacts are: 1) the zonasi system makes good schools less good because the main components in PPDB are no longer based on academic achievement, and 2) limits students in choosing schools.